Forest Flora of Kashmir: a Check List-I - Javeid, G. N. (Indian Forester, 1978)
The present communication is a systematic census of the woody species of Kashmir and Ladakh comprising the Forest Flora. The list includes both exotic and Indigenous species based on personal observations. In the list 375 species, both shrubs and trees, have heen included and their distribution in the forest divisions have been given. A note on the forest composition and phytogeography of the arboreal elements and its bearing on the introduction and distribution of the species has been given.